If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 7x = 56 + x Solving 2 + 7x = 56 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 7x + -1x = 56 + x + -1x Combine like terms: 7x + -1x = 6x 2 + 6x = 56 + x + -1x Combine like terms: x + -1x = 0 2 + 6x = 56 + 0 2 + 6x = 56 Add '-2' to each side of the equation. 2 + -2 + 6x = 56 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 56 + -2 6x = 56 + -2 Combine like terms: 56 + -2 = 54 6x = 54 Divide each side by '6'. x = 9 Simplifying x = 9
| 78-2x=8x+18 | | 2x-2=12x-72 | | 6x+32=14x-32 | | 11x-1=9x+5 | | -3-(-4x)=-4x+5 | | 20-5(4v-1)=-60 | | -4(5+6m)+14=-90 | | 2x-8=6x+36 | | -2x=-4x+24 | | 8(-4x-2)+10=-42 | | 12x+2=5x-(1-x) | | 17x=-5(4x-11) | | 10x+7+3x= | | 8(-4x-2)+10=42 | | -5x+10=66+3c | | 2(5x-8)=-6(x-8) | | -4x=12x+2 | | p-4=9+0 | | p-1=5p+3p-8 | | 12x+15=9x | | 9(10p-2)=27 | | 9(1op-2)=27 | | 2(5x-8)=6(x-8) | | 12x-(7x-6)=41 | | 6x+7=3x-11 | | 3(2x-8)=12 | | 4(n-15)=127 | | 6(x-1)=6x-1 | | 9x+7=5x+19 | | 4y+5=-7 | | 7b+3-4b=3-3(b+4) | | (x-4)(x+4)=(x+5)2 |